The language and meaning of media memes from a semiotic perspective - Arrobo-Agila, Juan Pablo; Gonzales Córdova, Mayra Paola; Barrazueta Molina , Patricio (European Public & Social Innovation Review, 2025)
Introduction: Memes have become a key resource for communication, making it possible to disseminate information quickly and to reach a young audience in search of specific content. This study analyses the effectiveness of memes in communication. Methodology: A quantitative and exploratory approach was used, with the technique of direct observation. Information was recorded through a form applied to a sample of 302 memes, analysing the visual elements, the message and the social, cultural or political context of each one. Results: The results show that memes generate active participation, and their effectiveness in communication depends on the relevance of the current context. Memes that reflect users' experiences have a greater impact. Discussion: The analysis reveals that memes are a powerful digital communication tool, leveraging both visual and linguistic content to connect with a broad and diverse audience on platforms such as TikTok, Instagram and WhatsApp. Conclusions: Memes are effective at communicating messages interactively, and their impact depends on the context and user experience.